Relationship between impulsivity, prefrontal anticipatory activation, and striatal dopamine release during rewarded task performance - Weiland, Barbara J. (2014)
Impulsivity, and in particular the negative urgency aspect of this trait, is associated with poor inhibitory control when experiencing negative emotion. Individual differences in aspects of impulsivity have been correlated with striatal dopamine D2/D3 receptor availability and function. This multi-modal pilot study used both positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) to evaluate dopaminergic and neural activity, respectively, using modified versions of the monetary incentive delay task. Twelve healthy female subjects underwent both scans and completed the NEO Personality Inventory Revised to assess Impulsiveness (IMP). We examined the relationship between nucleus accumbens (NAcc) dopaminergic incentive/reward release, measured as a change in D2/D3 binding potential between neutral and incentive/reward conditions with [(11)C]raclopride PET, and blood oxygen level-dependent (BOLD) activation elicited during the anticipation of rewards, measured with fMRI. Left NAcc incentive/reward dopaminergic release correlated with anticipatory reward activation within the medial prefrontal cortex (mPFC), left angular gyrus, mammillary bodies, and left superior frontal cortex. Activation in the mPFC negatively correlated with IMP and mediated the relationship between IMP and incentive/reward dopaminergic release in left NAcc. The mPFC, with a regulatory role in learning and valuation, may influence dopamine incentive/reward release.